Zmiana opodatkowania obrotu suszem tytoniowym akcyzą próbą ograniczenia szarej strefy w Polsce - Ćwiąkała-Małys, Anna; Piotrowska, Iwona (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
One of the dominant sources of budget income is the income from indirect taxes. The biggest share comes from goods and services tax and from excise tax. Inflows from excise tax on tobacco products trade are exposed to reductions due to illegal production of tobacco products and trade in dry tobacco in grey area. One of the state’s dutyies is to make such changes in legislation to reduce its growth. On the other hand, customs services should undertake operational and preventative actions that will protect state budget from reductions caused by illegal or non-taxed trade in dry tobacco.
Keywords: podatek akcyzowy; obrót suszem tytoniowym; szara strefa; służby celne